Adopting a Global AMR Target within the Pandemic Instrument Will Act as a Catalyst for Action. (2022) - Van Katwyk, Susan Rogers; Wilson, Lindsay; Weldon, Isaac; Hoffman, Steven J.; Poirier, Mathieu J.P.
Abstract: Ensuring that life-saving antimicrobials remain available as effective treatment options in the face of rapidly rising levels of antimicrobial resistance will require a massive and coordinated global effort. Setting a collective direction for progress is the first step towards aligning global efforts on AMR. This process would be greatly accelerated by adopting a unifying global target — a well-defined global target that unites all countries and sectors. The proposed pandemic instrument — with its focus on prevention, preparedness and response — represents an ideal opportunity to develop and adopt a unifying global target that catalyzes global action on AMR. We propose three key characteristics of a unifying global target for AMR that — if embedded within the pandemic preparedness instrument — could rally public support, funding, and political commitment commensurate with the scale of the AMR challenge.